2019
DOI: 10.5539/mas.v13n6p60
|View full text |Cite
|
Sign up to set email alerts
|

Utilization of Blogging Platforms and Acquisition of Entrepreneurial Skills for Self-Reliance Among Educational Technology Students in University of Calabar

Abstract: In this rapidly changing world, the quest for self-reliance has always been the desire of many nations especially in the present face of global economic challenge. This study centres on using blogging platforms for acquiring Entreprneurial skills for Self-reliance among Educational Technology Students in University of Calabar. The study utilized the descriptive survey design. Three research questions were raised and three research hypotheses were stated to guide the study. The population comprised all the 39 f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 1 publication
0
1
0
Order By: Relevance
“…Various reviews of specific technology can be found; for example, Fox et al ( 2018 ) built a criteria framework to review and evaluate serious entrepreneurial games; educational technologies applied to online and blended EE include technology-mediated to an intelligent method, e.g., computer aided instruction (CAI) (Petridou & Sarri, 2011 ), information technology (Nisheva et al, 2009 ) virtual and augmented reality (Sousa, 2019 ; Tarabasz et al, 2018 ), and big data (Obschonka & Audretsch, 2020 ). Our review of the articles which utilized technologies in EE encompasses the following: blog (Wagid & Oliver, 2017; Udosen & Upula, 2019 ), Wikis (Menkhoff & Bengtsson, 2012 ), Facebook (Chang & Lee, 2013 ; Ali et al, 2017 ), digital and non-digital serious games , course management system (Frederick, 2007 ; Wu et al, 2019 ) and MOOCs (Cirulli et al, 2016 ; Resei et al, 2018 ; Vorbach et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%
“…Various reviews of specific technology can be found; for example, Fox et al ( 2018 ) built a criteria framework to review and evaluate serious entrepreneurial games; educational technologies applied to online and blended EE include technology-mediated to an intelligent method, e.g., computer aided instruction (CAI) (Petridou & Sarri, 2011 ), information technology (Nisheva et al, 2009 ) virtual and augmented reality (Sousa, 2019 ; Tarabasz et al, 2018 ), and big data (Obschonka & Audretsch, 2020 ). Our review of the articles which utilized technologies in EE encompasses the following: blog (Wagid & Oliver, 2017; Udosen & Upula, 2019 ), Wikis (Menkhoff & Bengtsson, 2012 ), Facebook (Chang & Lee, 2013 ; Ali et al, 2017 ), digital and non-digital serious games , course management system (Frederick, 2007 ; Wu et al, 2019 ) and MOOCs (Cirulli et al, 2016 ; Resei et al, 2018 ; Vorbach et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%